2014
DOI: 10.1093/cid/ciu185
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Therapies in Rheumatoid Arthritis and the Risk of Opportunistic Infections: A Meta-analysis

Abstract: Among patients with RA, biologic agents are associated with a small but significant risk of specific OIs. This increase is associated with mycobacterial diseases and does not seem to affect overall mortality. Because OIs are a relatively rare complication of biologic agents, large registries are needed to identify the exact effect in different OIs and to compare the different biologic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
6
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 32 publications
3
85
6
7
Order By: Relevance
“…However, these remain rare, and the absolute risk is low. A small but significantly increased risk of OI (OR: 1.79; 95% CI: 1.17, 2.74) was reported in a meta-analysis of 70 trials including 32,504 patients involving all licensed biologics (infliximab, etanercept, adalimumab, certolizumab, golimumab, rituximab, tocilizumab, abatacept and anakinra) [85]. In all, there were 1.7 excess infections per 1000 patients treated amounting to a number needed to harm of 582.…”
Section: Risk Of Opportunistic Infections With Biologic Therapymentioning
confidence: 97%
“…However, these remain rare, and the absolute risk is low. A small but significantly increased risk of OI (OR: 1.79; 95% CI: 1.17, 2.74) was reported in a meta-analysis of 70 trials including 32,504 patients involving all licensed biologics (infliximab, etanercept, adalimumab, certolizumab, golimumab, rituximab, tocilizumab, abatacept and anakinra) [85]. In all, there were 1.7 excess infections per 1000 patients treated amounting to a number needed to harm of 582.…”
Section: Risk Of Opportunistic Infections With Biologic Therapymentioning
confidence: 97%
“…При этом встречаемость ППн у больных РА, получав-ших иФНО-α, не отличалась от таковой среди пациентов, находившихся на лечении БПВП -0,056 и 0,051 на 10 000 пациенто-лет соответственно [47]. По данным крупного метаанализа, включавшего более 30 000 больных РА, ППн имела место в 8 случаях, при этом не выявлено значимой ассоциации ее развития с применением ГИБП [57].…”
Section: воспалительные заболевания суставовunclassified
“…Treatment with TNF inhibitors as a group was associated with a higher risk of serious infection (odds ratio [OR], 1.42; 95% CI, 1.13-1.78) compared with placebo and/or traditional DMARD treatments [61]. Moreover, a metaanalysis that included 70 trials has confirmed the increased risk of opportunistic infections among RA patients treated with biological agents [62].…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…In a meta-analysis of 5669 RA patients treated with biological agents, no significant differences were found for PCP. Only eight cases of PCP were reported: six in patients receiving biologics and two among controls [62]. However, postmarketing surveillance in Japan revealed that 35 (0.47%) of 7522 patients receiving IFX, 25 (0.18%) of 13,894 patients receiving ETN, 26 (0.34%) of 7740 patients receiving ADA, 14 (0.2%) of 7901 patients receiving TCZ, and 4 (0.1%) of 3985 patients receiving ABA developed PCP ( Table 2).…”
Section: 5mentioning
confidence: 99%